101 Dalmatians - Herek, Stephen (Pasig City : Viva Video.)
Opening to packed theaters and rave reviews worldwide Disney's live-action smash hit 101 DALMATIANS brings the floppy-eared fun and fiendish exploits of the world's most vampy villainess home to your family! In a perfectly wicked performance, Glenn close stars as Cruella De Vil, the fur-loving fashion maven who's obsessed with obtaining Dalmatian pelts for her new line. Cruella's fashion designer Anita and her husband Roger are delighted when their Dalmatians Pongo and Perdita become proud parents of a litter of adorable puppies. But after Cruella conspires with her two bumbling henchmen to kidnap the pups, the fur begins to fly, building to one of the greatest rescue adventure stories ever told! Based on Disney's beloved animated Classic, and produced by Home Alone's John Hughes, 101 DALMATIANS unleashes movie magic the whole family will love time after time!